Transient thermal analysis of solid propellant rocket motor / Dr. Ts. Ahmad Hussein Abdul Hamid … [et al.] - Abdul Hamid, Ahmad Hussein; Mohamad Aliman, Mohamad Haziq; Salleh, Zuraidah; Sujana, Mohammad Juani; Ismail, Osmera; Muhammad, Mohamad Amirul; Mohd Fazli, Mohamad Akmal (Smart Manufacturing Research Institute (SMRI), 2022)
The creation of stable, high-temperature combustion of propellant is critical in the operation of rocket engines. Due to the high operating temperature and pressure, it is likely that the structural strength of the rocket’s engine component will deteriorate. This will eventually increase the likelihood of mission failure. Hence, conducting a transient thermal analysis of the components while designing the rocket engine is critical. The thermal analysis can also be used to estimate the thermal energy distribution in parts that come into contact with the heat flow induced by propellant combustion, assisting in the selection of the correct material and geometry for rocket nozzle construction. Thermal analysis is crucial for the design of reusable engines, especially as some rocket engines are intended to be used only once, at least. The present study is intended to analyse the transient heat transfer by observing the temperature distribution across the material and components of the rocket, including the propellant, inhibitor, nozzle, and outer casing. Besides that, the study was aimed at investigating the rate of temperature rise within a few seconds of rocket firing. The analysis revealed that the inner surface of the rocket engine casing had reached a temperature as high as 181.8 °C within 0.6 s of the rocket firing. It is also found that the surface temperature increases almost linearly with time.